Clinicopathologic Features, Diagnosis, and Characterization of the Immune Cell Population in Canine Choroid Plexus Tumors - Dalton, Martha F.; Stilwell, Justin M.; Krimer, Paula M.; Miller, Andrew D.; Rissi, Daniel R. (Frontiers in Veterinary Science, 2019)
The World Health Organization characterizes human choroid plexus tumor (CPT) as papilloma (CPP), atypical CPP (ACPP), and carcinoma (CPC). CPCs can disseminate via cerebrospinal fluid and be mistaken for metastatic carcinoma, creating a diagnostic challenge. Kir7.1 immunohistochemistry (IHC) is a highly reliable tool for diagnostic confirmation of CPTs and their differentiation from metastatic carcinomas in human beings and dogs. This study describes the neuropathology, Kir7.1 staining profile, and the immune cell population within the tumor microenvironment in 11 CPTs in dogs. Archived tissue sections with a diagnosis of CPT were examined and immunolabelled with Kir7.1 for diagnostic confirmation. The number of Ki67-positive neoplastic cells was calculated in 2.4 mm2 (equivalent to 10 FN22/40X fields), and a mean value was generated for each neoplasm. IHC for CD3, CD20, MAC387, and Iba1 was performed for immune cell characterization, and the number of stained cells for each antibody was counted in 2.4 mm2, generating individual cumulative values for each antibody. T-tests with Bonferroni correction evaluated IHC differences between tumor types, and Spearman's rank correlations evaluated relationships among IHC markers. Kir7.1 immunoreactivity was intense at the apical cell membrane in CPPs and ACPPs, and at the apical cell membrane and cytoplasm in CPCs. Ki67 immunoreactivity was detected in all cases. CD3+ and CD20+ lymphocytes trended together (p = 0.005) and were present within and around all CPTs. Five cases had intravascular MAC387+ monocytes. Iba1 immunoreactivity was robust within and around all tumors. Statistical differences in immune cell markers were not found among tumor types. As previously reported, Kir7.1 is a reliable antibody for the diagnosis of canine CPTs. Although immune cells were present in all cases, no significant associations were found between the type of cells and tumor diagnosis. The characterization of the immune cells within CPTs could be useful in future studies involving immunotherapy.